Sustainable Urban Mobility Towards Smart Mobility: the Case Study of Bari Area, Italy - Niglio, Raffaella; Comitale, Pier Paolo (TeMA - Journal of Land Use, Mobility and Environment, 2015)
In the last decades, sustainable mobility policies have seen a growing interest. Furthermore, in the international debate, this concept has increasingly been linked to the most innovative one of smart mobility, which is part of the more general paradigm of Smart City. The primary goal of the work is to make a review of policies, programs, projects for sustainable urban mobility and of smart mobility solutions in Bari area. The second goal is to make an assessment on trends of urban mobility in order to evaluate its sustainability and smartness. A comforting picture, focused on matching the local strategies to European programs, is shown. Finally, a consideration on how the framework “smart” may improve urban mobility planning is proposed.